Psychological Interpretation of Song Lyrics by Putri Ariani's Single - Narisa, Vivi; Erni, Erni (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Songs are an appreciation of literary works that have emotional communicating elements. As a result, songs may be a form of communication for singers and composers to express their feelings to listeners. One of them is the song Putri Ariani, which has several singles. The aim of the research is to describe, analyze, and interpret the psychology of the song lyrics in the single Putri Ariani. The method used in this research is descriptive qualitative. Data collection techniques include (1) listening to the song carefully, (2) noting the song lyrics carefully, and (3) understanding the psychological aspects of the song. Data analysis uses Schleirmacher's hermeneutical approach. The conclusion of this research is that the lyrics written in Putri Ariani's single were created from the author's feelings and experiences so lyrics emerged that were touching and accepted by the public. The lyrics he wrote move from the author's own circumstances. Apart from that, it depicts hope, sadness, disappointment, admiration, and love. The implications of the research results can be used in the development of psychological interpretation studies (Schleiermacher hermeneutics) and can be useful in the field of education. For example, when studying poetry, this song can also be played to stimulate students' imagination and provoke students' understanding.